The Age of Full AI in Education: Redefining Learning through Intelligent Technology - Rosyidah Dzunur'aini; Abroto; Abduhakim Kaje Yamkee; Yessika Destiana Lahabu; Intan Dewi Mawardini (International Journal of Basic Educational Research, 2025)
This research aims to identify and evaluate how the use of Artificial Intelligence and machine learning can be optimized in the educational context and its impact on educational development. The focus of this research is to analyze how Artificial Intelligence can be used to enhance student understanding and engagement through visual-based learning materials. Assessing the potential of artificial intelligence in personalizing learning experiences and providing adaptive feedback for students. Identifying challenges and barriers in the implementation of these two technologies in the educational context. Evaluating the impact of integrating Artificial Intelligence on the quality of learning and student learning outcomes. This research examines the transformative potential of full AI implementation across various aspects of education, ranging from personalized learning, automation of teaching processes, enhancement of assessment accuracy, to the creation of adaptive learning environments. Based on recent developments in machine learning, natural language processing, and intelligent tutoring systems, this study provides a comprehensive review of how AI is revolutionizing the educational landscape. This analysis also addresses crucial challenges accompanying full AI adoption, including ethical issues, data privacy, algorithmic bias, and the shifting roles of educators. By analyzing current implementations and future trends, this research proposes a conceptual framework for inclusive, ethical, and resilient smart education in the face of changing times. Ultimately, this study asserts that the comprehensive utilization of AI in education is not merely an option, but an urgent necessity to redefine the meaning of learning in a constantly changing world.